The effect of eurycoma longifolia jack root extract on serum lipids of rats - Faisal, Ghasak Ghazi; Mustafa Al-Ahmad, Basma Ezzat; Mustafa, Nazih Shaban; Najmuldeen, Ghazi Faisal; Althunibat, Osama Yousef (2014)
Eurycoma Longifolia jack (E.L) has many useful biological activities and there is continuous research to find new effects of this plant. Objectives: to investigate the effect of E.L. extract on serum lipids of rats. Methodology: 40 mature albino Wistar rats were used. Baseline blood samples were analyzed for serum lipids; cholesterol(chol) ,High density lipoprotein (HDL) and Low density Lipoprotein (LDL). The rats were then kept for 4 weeks on high fat diet. After that period , serum lipid analysis was done again. Then the rats were divided into 2 groups (A,B) and kept on the same high fat diet and additionally received twice daily treatment of E.L. root extract with a dose of 5and 10mg/Kg for group A and B respectively for 4 weeks.Lipid analysis was done again. Results: There was a statistically significant rise in the cholesterol level from the baseline of 136 to 192mg/dl after feeding with high fat diet. However, after treatment with E.L. extract, Both group A and B showed a significant decrease in the cholesterol level 142,139 mg/dl respectively. Regarding LDL and HDL, group A showed a more favorable outcome because in group B there was a sharp drop in the HDL and a rise in LDL level which makes the LDL/HDL ratio increase well above the recommended safety limits. Conclusion: E.L. root extract may be used for lowering of serum cholesterol. However, the dose should be adjusted to prevent unwanted changes in HDL and LDL levels.